A Feminist Reframing of Bullying and Harassment: Transforming schools through critical pedagogy - Meyer, Elizabeth (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2008)
AbstractThis article aims to reformulate existing understandings of bullying behaviours in secondary schools, by applying a critical feminist lens to patterns of verbal and psychological harassment among students. Through this understanding, educators may better understand the causes of (hetero)sexist, transphobic, and homophobic behaviours. With a more complex awareness of these power relations, teachers, teacher educators, and educational leadership scholars will be offered critical approaches to help them transform the oppressive cultures of schools.